2012
DOI: 10.1261/rna.032748.112
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of aptazyme-regulated gene expression in a cell-free translation system: Modeling of ligand-dependent and -independent expression

Abstract: Aptazymes are useful as RNA-based switches of gene expression responsive to several types of compounds. One of the most important properties of the switching ability is the signal/noise (S/N) ratio, i.e., the ratio of gene expression in the presence of ligand to that in the absence of ligand. The present study was performed to gain a quantitative understanding of how the aptazyme S/N ratio is determined by factors involved in gene expression, such as transcription, RNA self-cleavage, RNA degradation, protein t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Nonetheless, the variety of ligands that cell-free riboswitches have been engineered to detect are quite broad compared to cell-based riboswitches. Although theophylline has been, by far, the most popular trigger molecule, cell-free riboswitches that respond to biotin, 77 tetramethylrhodamine (TMR), 46,78,96 flavin mononcleotide (FMN), 88,89,97 cGMP, 36,87 TPP, 39,42 fluoride, 48 histamine, 45 dopamine, 46 thyroxine, 46 sulphorhodamine B, 88 Hoechst dye 33258, 76 tobramycin, 76 tetracycline, 88,97 and pentadeoxyribonucleotides 114 have been designed (Tables 1 and 2). With the exception of histamine, however, these cell-free riboswitches have been constructed using known aptamers from natural riboswitches or discovered Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, the variety of ligands that cell-free riboswitches have been engineered to detect are quite broad compared to cell-based riboswitches. Although theophylline has been, by far, the most popular trigger molecule, cell-free riboswitches that respond to biotin, 77 tetramethylrhodamine (TMR), 46,78,96 flavin mononcleotide (FMN), 88,89,97 cGMP, 36,87 TPP, 39,42 fluoride, 48 histamine, 45 dopamine, 46 thyroxine, 46 sulphorhodamine B, 88 Hoechst dye 33258, 76 tobramycin, 76 tetracycline, 88,97 and pentadeoxyribonucleotides 114 have been designed (Tables 1 and 2). With the exception of histamine, however, these cell-free riboswitches have been constructed using known aptamers from natural riboswitches or discovered Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1B) were further analyzed by Kobori et al in a modified PURE system for the purpose of optimizing riboswitch performance based on kinetic modeling. 39 It should also be noted that synthetic riboswitches developed based on the same design strategy have been shown to function in E. coli by Ogawa and Maeda, 40 and the Hartig group. 12,13 In another study, Ogawa and Maeda tethered the theophylline-responsive aptazyme to the 5 0 end of a nonsensesuppressor tRNA (sup-tRNA) to regulate translation read-through of a gene that contains an amber stop codon in a customized PURE system (Fig.…”
Section: Aptazyme-based Riboswitchesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have relied on the aptamer to characterize riboswitches and logic gates in a wide variety of species. The aptamer has also been used for in silico studies or optimization of riboswitch function and kinetics. Initial work with theophylline ribozymes demonstrated that ribozymes could be rationally engineered to function in vitro . ,, The ability to engineer biology in a modular fashion was then demonstrated by linking the aptamer to a number of different catalytic RNAs, including the hammerhead, X motif, Tetrahymena group I, and HDV ribozymes through a 9-nt communication module . OR and AND logic gates were also constructed for an in vitro colorimetric assay of theophylline and cGMP using DNA-tethered gold nanoparticles .…”
Section: Applications Involving the Theophylline Aptamermentioning
confidence: 99%